The Difficulties Faced by Graduate Students when Using the (SPSS) in their Research Projects: A Field Study on Graduate Students at M’sila University. - برباخ رابح; عمور عمر (sports creativity, 2025)
This study’s objective is to shed light on the difficulties encountered by graduate students when using the SPSS system in their research projects, to determine their relative weight, and whether these difficulties are due to gender, training domain, level, and secondary school major. The researcher used the descriptive method, and signed a 45 items questionnaire to identify the difficulties. The questionnaire items are distributed on two main axes: the difficulty of the subjects of statistics and measurement, and the difficulty of using the SPSS system. After examining itsreliability and validity, the tool was used with a sample of (130) male and female students. The statistical tools used are the Frequencies, percentages, the t-test for significance of mean differences, one-way analysis of variance, and Tukey's test for post comparisons. The results of the study revealed the difficulties that graduate students face when using the SPSS system, with a percentage of: 69.68%. The results also showed that there are statistically significant differences attributed to gender in favor of female students compared to male students. There were no statistically significant differences in the difficulties attributed to the training domain, except for the first axis, where recorded mean differences were in favor of humanities and social sciences compared to physical and sports activities sciences and techniques. The results did not show the differences in difficulties attributed tosecondary school major (literary, scientific). The results showed that there were statistically significant differences in the total score of the tool and in its two sub-axes and in favor of the lower levels students compared to the higher ones (Bachelor, Master, PhD)